Improvement in hardwood bonding strength of polyvinyl acetate emulsion by controlling bimodal particle size distributions - Andrea Payares; Adriana Mendoza; José Antonio Gil; María Rodríguez (Results in Surfaces and Interfaces, 2025)
It is challenging to improve the adhesive strength of a hardwood glue due to the low porosity of the substrate, which impedes the full penetration of fluids into it. To have adhesive strength, the adhesive must be formulated using a polymeric matrix with the right properties for adherence to a specific substrate. In this study, an emulsion of polyvinyl acetate (PVAc) with bimodal particle size distribution was developed using polyvinyl alcohol (PVA) as protective colloids by redox emulsion polymerization, resulting in a stable emulsion of 56.09 percent of solids, 67,200 cP viscosity, and an average particle size of 1.85 μm. The bimodal base was also characterized by Attenuated Total Reflection - Fourier Transform Infrared Spectroscopy (ATR-FTIR) and Scanning Calorimetry (DSC). With this emulsion, a hardwood glue with 47.80 percent of solids, 21.760 cP viscosity, and an average grab strength of 17.63 MPa was formulated, corresponding to an increase of 5.86 MPa compared to a similar glue with monomodal particle size distribution. Additionally, for the study of the adhesion of the glue to the carob wood, the variation of the contact angle in time was studied, which showed a difference of 53.80° angle (0–25 min) for the glue formulated with the bimodal base, compared to a value of 23.81° angle (0–25 min) for the glue manufactured with the monomodal base under the same conditions, which indicates a better behavior of the bimodal adhesive on the carob wood.